Identifying the Employment Skills Among Malaysian Vocational Students: An Analysis of Gender Differences - Ismail, Irwan Mahazir; Ahmad, Nor Aziah; Amiruddin, Mohd Hasril; Ismail, Mohd Erfy; Harun, Hairuddin (Journal of Technical Education and Training, 2019)
Employability and the creation of a knowledge-based economy have become fundamental concerns in many countries, including Malaysia. Realizing the need to achieve a high-income economy, the Malaysian Government through its Eleventh Malaysia Plan (2016-2020) is transforming Technical and Vocational Education Training (TVET) by enabling industry-led approach is crucial to produce skills human capital that meet the industry demand and support the migration of all economic sectors towards knowledge intensive activities, in line with the aspiration to become a high-income nation by 2020. Technical and Vocational Education can play a major role in providing future workforce with employability skills. Therefore, the research aims to examine the differences in competency perceived level by gender for vocational students majoring in hospitality. Questionnaires were distributed to 841 hospitality students in five regions in Malaysia. Descriptive statistic and independent sample T-Test were used to analyse the data. The findings show that there is no significant difference between male and female. The mean score of male is higher than mean score of female. Thus, the result provides evident that male is more competent in hospitality employability skills compared to female student in vocational colleges. The findings provide insights to curriculum developers and policy makers on the appropriate interventions that need to be taken to improve the employability skills of the graduates.